The Effect of Anesthesia on Postoperative Cognitive Dysfunction - Miro Bilić; Martina Lukšić; Martina Miklić Bublić; Zrinka Orešković; Davor Mijatović; Vilena Vrbanović Mijatović (Acta Clinica Croatica)
Postoperative cognitive dysfunction (POCD) is a newly developed cognitive function deficit after surgery. The aim of the study was to determine the incidence of POCD after anesthesia and possible risk factors. A prospective study was conducted on 90 patients scheduled for elective surgery under general (60 patients) or regional (30 patients) anesthesia. Each patient completed the Montreal cognitive assessment (MoCa) test the day before and the day after surgery. Data on comorbidities, previous COVID-19 infection, demographic and anesthesia related data were also collected. The day after surgery, POCD defined according to the 2 scores rule was present in 38 (42.2%) patients. A lower level of education (p=0.023), previous COVID-19 infection (p=0.032), higher Charlson comorbidity index (CCI) (p=0.014), and general anesthesia (p=0.035) were identified as risk factors, whereas a statistically significant negative correlation with preoperative (p=0.001) and postoperative result (p=0.001) was proven for age. The results indicated that a significant proportion of patients after general or regional anesthesia developed POCD depending on patient education, CCI, COVID-19 infection, and type of anesthesia. It was also shown that older age correlated with poorer MoCa test result independently of anesthesia. These factors can be identified before the procedure under anesthesia, thus offering the possibility of adjusting anesthesia and postoperative care in patients at risk of developing POCD.